Adsorption of toxic metal ion in agricultural wastewater by torrefaction biochar from bamboo shoot shell. (1st March 2022) - Hu, Hui; Zhang, Jiayuan; Wang, Tian; Wang, Pei
Abstract: The purpose of this study is to design the oxygen-rich biochar through torrefaction for the detoxification of toxic metals in agricultural wastewater. The optimum operation parameters, kinetic, isotherm, and thermodynamic study are investigated. The influence of torrefaction biochar on toxic metal adsorption is analyzed by using site energy distribution theory. The adsorption mechanism is analyzed by Fourier transform infrared spectroscopy (FTIR) and X-ray photoelectron spectroscopy (XPS). Two-dimensional FTIR analysis and density functional theory (DFT) calculations are further used to inquire the prior interactional sequence between surface functional groups and poisonous metals. The results indicate that the sorption mechanism of Cr(VI) is ascribed to the adsorption-coupled reduction mechanism that some redox-active components provide electrons for Cr(VI) reduction. Surface complexation is mainly the Cu(II) sorption mechanism with a small content of Cu(II) reduction to Cu(I). The catechol hydroxyl group is the main form of phenol-OH on the TBC surface. Graphical abstract: Image 1 Highlights: 1. Catechol hydroxyl group is the main form of phenol-OH on the TBC surface. 2. The interaction between Cr(VI) and TBC is adsorption-coupled reduction. 3. The interaction between Cu(II) and TBC is surface complexation.